Influence of Cycling Profile, Depth of Discharge and Temperature on Commercial LFP/C Cell Ageing: Cell Level Analysis with ICA, DVA and OCV Measurements. Issue 11 (30th June 2020) - Simolka, M.; Heger, J.-F.; Traub, N.; Kaess, H.; Friedrich, K. A.
Abstract : This paper uses several techniques to monitor the ageing of commercial LiFePO4 cells, which are cycled at 55 °C and −20 °C at various depths of discharge. Ageing at lower depth of discharge leads to higher capacity fading, as compared to higher depth of discharge. The highest capacity fading is observed using 50% depth of discharge for cycling at 55 °C, while the lowest capacity fading is observed for the cells aged at 100% depth of discharge when cycled at −20 °C. Using incremental capacity analysis and differential voltage analysis the capacity fading is monitored and underlying ageing mechanisms are described. The loss of lithium inventory and the loss of active material, especially on the cathode side, are the major degradation mechanisms for the cells. The first incremental capacity analysis peak of the discharge process can be used in our case to predict remaining life and cell capacity.